VCO Production from Fresh Old Coconut Bunch by Circulating and Pumping Method - Muhamad Maulana Azimatun Nur; Joko Mulyono; Danny Soetrisnanto (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
VCO (Virgin Coconut Oil) is one of coco-diesel source, made without high heating and chemicals. Commercial processes production, such fermentation and centrifugation usually need more time and expensive in cost and investment. Circulating by pumping through a nozzle is a new process method invented to produce VCO. The process followed by coalescence method, breaking emulsion by hitting particles through pipe and nozzle. The problem of this method was that the product gave lower yield than another method and not yet qualified. This research was purposed to discover correlation between pressure and time of circulation variables against yield and content (FFA, Peroxide, water content) represented by SNI (national Indonesian standard). Producing VCO initiated by producing coconut milk from fresh old coconut, then each 1 litre milk were pumped through the pipe and nozzle with variation of circulations pressures and time. The results were decanted for 10 hours so the oil and water would be separated. The oil at upper layer was taken as final product. Then the last step was analysed the oils and oil cake (blondo). The results showed that pressure and time of circulating variables gave impact to the yield. On optimum variables, 2 atm pressure and 15 minutes of circulating gave better results with 97% yield. This operating variables also affecting oil quality. The minimum water content is 0.1%, free fatty acid is 0.18% and peroxide value is 2 mg/kg eq. The results showed that all of parameters meet the SNI standard.